Plan de Negocio para la creación del restaurante DAEBAK especializado en comida Coreana - Manjarrez Martinez laura Marcela; Pallares Vanegas Gloria Marcela (Universidad Antonio Nariño, 2024)
This business plan focuses on the technical modeling of Daebak Restaurant, a space that gives samaris the opportunity to taste Korean food, being the first-class restaurant in the city of Santa Marta. With the development of this restaurant, it is intended to respond to the basic need for people's food, and also to provide them with an environment where they can share with family and friends. This is how we are invited to promote the interest in a new culture, which today is a global trend, thanks to the influence of the Hallyu industry, all this will be carried out through a linear organizational model. This business plan implements a mixed research typology, as a qualitative and quantitative model of recognition is carried out, for this purpose a number of primary and secondary instruments are used, which seek a comprehensive analysis of the objects studied and formulated. At the institutional level, the study is conducted in accordance with the guidelines of the field of organizational management research.